Efek penggunaan ulang larutan fiksatif formalin pada kualitas preparat histopatologi dan jumlah limbah yang dihasilkan - Hardi, Zon; Wiryanti, Wiwin; Durachim, Adang; Rahmat, Mamat (Current Biomedicine, 2024)
Background: Neutral buffered formalin (NBF) 10% fixative solution is widely used in histopathological slides. The fixation process generates liquid waste of NBF 10% and solid waste of tissue remnants. Objective: The research aimed to assess the reuse of NBF 10% fixative solution on the quality of histopathological slides and calculate the amount of waste produced. Methods: Treatments included single-use of fixative solution (control), reuse for 1, 2, and 3 times. Ten sample slides were prepared for each treatment, consisting of intestinal tissue, uterine fibroids, prostate, uterus, ovarian cyst, portio vaginalis cervicis, thyroid, rectum, breast fibroadenoma, and gallbladder tissues. Tissues were fixed with NBF 10% and processed histologically with hematoxylin-eosin staining. Liquid waste of NBF 10% and solid waste of tissue remnants were quantified. Histopathological slide quality was measured under a microscope for nuclear and cytoplasmic clarity, staining intensity, and color uniformity. Results: Control slides exhibited good quality with clearly blue-stained nuclei, pink cytoplasm, no color accumulation, and uniform staining across fields of view. Reused NBF 10% slides experienced a decrease in quality compared to the control but were still usable for diagnosis. Slides reused 2 and 3 times showed poor quality, making diagnosis difficult. Fixation resulted in 299.0 liters of liquid waste of NBF 10% and 64.9 kilograms of solid tissue remnants. Conclusion: Reusing NBF 10% decreases histological slide quality, though reuse once still allows for diagnosis. Reusing 10% NBF for tissue fixation can reduce the liquid waste of fixative solution and solid tissue waste.